Kepastian Hukum Syarat Mantan Narapidana Calon Anggota DPD Pasca Putusan Mahkamah Konstitusi Nomor 12/PUU-XXI/2023 - Artyo, Yovereld Alexetty; Salman, Radian (Universitas Batanghari Jambi, 2024)
General Election Contestation (Election) is one indicator of the implementation of the ideals of a democratic country. A democratic state certainly cannot be separated from the ideal of the rule of law, because in fact the state of law and democracy go together. This is because a state administration must be based on applicable law, and the law is implemented as much as possible for the community. In order to support the implementation of the rule of law in accordance with the wishes of the people, the concept of democracy is a concept that is no less important. In the context of statehood, it is appropriate for the voice of the people to be represented by representatives of the people in parliament, both central and regional. The people's representatives are elected through elections by stating the conditions that must be met. However, the conditions listed seem inconsistent and there are even aggrieved parties so that they do not show legal certainty. The purpose of this study is to see aspects of legal certainty regarding the requirements for ex-prisoner who want to run in election contestations, especially the selection of individual candidates for DPD members. The method used in this research is juridical-normative legal research or commonly called doctrinal legal research with statute approach and conceptual approach. The results showed that the requirements for ex-prisoner who wanted to run in the election contestation had changed several times as a result of material tests in the Constitutional Court. The change in requirements is the result of an inconsistent change in attitude by the Constitutional Court towards the existence of ex-prisoner requirements when they want to run in election contestations, including the selection of individual candidates for DPD members.